Vitamin D Analogues Tacalcitol and Calcipotriol Inhibit Proliferation and Migration of T98G Human Glioblastoma Cells. Issue 2 (25th April 2018) - Emanuelsson, Ida; Wikvall, Kjell; Friman, Tomas; Norlin, Maria
Abstract: The active form of vitamin D (1α, 25‐dihydroxyvitamin D) acts as a steroid hormone and binds to the vitamin D receptor. This receptor is expressed in most cell types including cells in the central nervous system (CNS). Vitamin D has several functions in the body including effects on brain development, neuroprotection and immunological regulation. It has been shown that vitamin D has antiproliferative activities in different cancer cell lines. Tacalcitol and calcipotriol are synthetic analogues of 1α, 25‐dihydroxyvitamin D with reduced effect on calcium metabolism. The aim of this study was to analyse the effects of tacalcitol and calcipotriol on cell viability, proliferation and migration in the human glioblastoma cell line T98G. Glioblastoma is the most lethal type of primary tumours in the CNS. Both analogues decreased cell viability and/or growth, dose‐dependently, in concentrations between 1 nM and 10 μM. Manual counting indicated suppressive effects by the vitamin D analogues on proliferation. Treatment with tacalcitol strongly suppressed thymidine incorporation, indicating that the vitamin D analogues mainly inhibit proliferation. Also, effects on cell migration were measured with wound‐healing assay. Both calcipotriol and tacalcitol reduced the migration rate of T98G cells compared to vehicle‐treated cells. However, they had no effect on caspase‐3 and ‐7 activities, suggesting that their mechanism of action does not involve induction of apoptosis. The current results indicate that the vitamin D analogues tacalcitol and calcipotriol strongly reduce proliferation and migration of human glioblastoma T98G cells, suggesting a potential role for this type of compounds in treatment of brain cancer.